Modulation of the Precipitation Isotopes by the Dynamic and Thermodynamic Variables of the Atmosphere in Southern Parts of India. Issue 8 (22nd August 2022) - Fousiya, A. A.; Aravind, G. H.; Achyutan, H.; Chakraborty, S.; Chattopadhyay, R.; Datye, A.; Murkute, C.; Lone, A. M.; Kripalani, R. H.; Yadava, M. G.; Mohan, P. M.
Abstract: The isotopic values of rainfall in the southern parts of India exhibit strong seasonality. Such a contrast in isotopic values arises mainly due to the seasonal reversal of the monsoon winds. During the summer monsoon season, moisture is primarily transported from the Arabian Sea, while during the winter, it is sourced mainly from the Bay of Bengal. Additionally, atmospheric processes contribute to these differences. We collected precipitation samples from a southern Indian site and two neighboring island locations to study their isotopic characteristics from intra‐seasonal to seasonal timescale. Oxygen isotopes in the marine environment seem to respond differently to the surface and tropospheric temperature than their counterparts from the land region. The seasonal isotopic gradient in the marine environment appears to be modulated by the tropospheric temperature anomaly. Oxygen isotopic values showed a strong association with the Webster‐Yang monsoon index. Two distinct clusters were formed when the oxygen isotopes were plotted against the above‐mentioned monsoon index. The formation of these clusters indicates the precipitation isotopes' response to moisture dynamics, which significantly change during the transition phase of the southwest to the northeast monsoon. Finally, we examine the potential of the precipitation isotopic records in studying the monsoon process, viz, the use of precipitation isotopes in characterizing the thermodynamical properties of the atmosphere and estimating the summer monsoon withdrawal phase. Plain Language Summary: Atmospheric parameters such as temperature, rainfall, humidity, wind circulation, etc., vary significantly across the seasons. Such kind of variations or the seasonality also varies from place to place. The heavy to light isotopic distributions of hydrogen and oxygen atoms in atmospheric water also differ considerably from summer to winter, termed isotopic seasonality (defined here as Δδ 18 O). This feature manifests well in southern peninsular India, wherein the summer monsoon season is characterized by higher isotopic values relative to the winter season. Monsoon circulation is south‐westerly during the summer and north‐easterly during the winter. These two opposing circulation regimes cause isotopic seasonality in south peninsular India. Meteorological parameters such as rainfall, wind speed, etc., display sharp changes during the summer monsoon onset in early June. But they change rather slowly during the transition from summer to winter monsoon season around late September–early October. As a result, the estimation of the summer monsoon withdrawal date may have considerable uncertainty. It is proposed that applying the isotopic technique may be potentially helpful in reducing such an uncertainty. Key Points: Precipitation isotopic time series at the northern Indian Ocean reveal strong seasonality, driven by monsoon thermodynamics Two well‐defined clusters are formed when δ 18 O is plotted against the Webster‐Yang circulation index The formation of clusters is indicative of isotopic response to moisture dynamics